Diplomatic Activities and Meetings Between Petar I Karadjordjević and Nikolaj II Romanov on the Eve of the Balkan Wars - Zarković, Vesna (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The May coup and the change of dynasties in the Kingdom of Serbia brought the state into an unenviable position. The aggressive Austro-Hungarian policy, which endangered Serbian interests, came to the fore. The annexation of Bosnia and Herzegovina and the mood that was present in the diplomatic circles of Austria-Hungary forced the Kingdom of Serbia to become active in the foreign policy field and get closer to Russia. Although there was a need and initiative of politicians in Serbia to organize a meeting between King Petar I Karadjordjević and Russian Tsar Nikolaj II Aleksandrovič Romanov, this idea did not materialize. Russia was busy in the war with Japan, but after resolving the issue in the East, it became more actively involved in the events in the Balkans.At that time, Russian plans related to San Stefano Bulgaria were an obstacle in the rapprochement between the Kingdom of Serbia and Russia. The ruler of Bulgaria Ferdinand pursued a changing policy that could very easily lead to rapprochement with Austria-Hungary. In contrast, relations between Serbia and Austria-Hungary had strained, prompting Serbian diplomats to ask the Russian side for a meeting between the two rulers. The Government of the Kingdom of Serbia received great support from Nikola Hartving, the Russian ambassador to Belgrade who was appointed to this post in 1909. His understanding of Balkan issues coincided with Serbian interests.Thanks to the engagement of the Russian ambassador, but also thanks to Serbian diplomacy, for the first time in 1910, King Petar I Karadjordjević and Tsar Nikolaj II met in Petrograd. Along with numerous politicians, the King was accompanied on that trip by Nikola Pašić and Milovan Milovanović, who asked the Russian Minister of Foreign Affairs, Aleksandar Petrovič Izvoljski, for support in concluding the Balkan Alliance. At that moment, Izvoljski stated for the first time that injustice had been done to Serbia by the San Stefano Treaty and expressed the need to change it. Such an attitude of Russian diplomacy paved the way for Serbia's reliance on Russia, which represented its support for the creation of a Balkan alliance.
Keywords: Kingdom of Serbia; Russia; Petar I Karadjordjević; Nikolaj II Romanov; diplomatic activities; Balkan Alliance